Covid-19 Effect to Return On Equity on European Football Club - Bhilawa, Loggar; Aisyaturrahmi; Prastiwi, Dewi; Prasetyo, Eko (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to determine and analyze whether or not there are differences between financial ratios before and after the COVID-19 pandemic in 22 professional football clubs in Europe for the period 2019 to 2020. The financial ratio used is return on equity. This study uses a quantitative method using a comparative approach, because the data used are in the form of numbers and analyze using statistics and this research is to compare the similarities and differences of 2 or more properties and objects studied in a certain frame of mind. The data analysis method used was the paired sample t-test and the Wilcoxon signed rank test, which had previously been tested for normality. The results of data analysis show that there is a significant difference between the financial ratios of football clubs before and during the COVID-19 pandemic.